Increasing Returns and Spatial Unemployment Disparities - Jens Suedekum (European Regional Science Association (ERSA), 2003)
Regional differences in unemployment rates in the EU, both within and across member countries, are far more pronounced than regional income disparities. Yet, standard models of the new trade and location theories (new economic geography, new trade theory etc.) usually assume full employment and can thus not provide a coherent explanation for spatial unemployment differences. Regional labour market theories like the 'wage curve'-approach on the other hand fail to account for regional agglomeration of economic activity, which is one of the most salient features of the spatial economic structure in the EU. The model in this paper analyses regional agglomeration and regional unemployment in an unified approach, as it combines a wage curve with a technology exhibiting localised increasing returns to scale. The main result of the paper is the prediction that regional unemployment rates closely resemble the core-periphery structure of regional incomes per capita. This matches the stylised facts about the geographical configuration of production and employment in the EU.
Keywords: 330